صراع الثٌقافي الأصيل والمعرفي المستعار في النّقد العربي الحديث - صايبة,سعاد (University of Eloued جامعة الوادي, 2024)
Abstract: This research seeks to contemplate some Arab critical visions in the interaction of the original and the borrowed in them, based on the fact that cultural death is like physical death, but rather it is more dangerous to the existence of peoples, because the identity elements of culture, like the soul to the body, which explain the rejection of every outsider. This rejection may It accepted with time, by formation of a new consciousness of it, or never accepted, because it touches culture in depth. The rejection or acceptance and what is in between, are the positions of criticism known by modern and contemporary Arab criticism.
Keywords: الإثنيّة; التّفكير النّقدي; نقّد ما بعد الحداثة; Ethnicity; Identity; Critical thought; Culture; Postmodern Criticism